Flood Impact Assessments on Transportation Networks: A Review of Methods and Associated Temporal and Spatial Scales - Rebally, Aditya; Valeo, Caterina; He, Jianxun; Saidi, Saeid (Frontiers in Sustainable Cities, 2021)
A region's transportation sector is vital to its economic and social health. Transportation systems are also influenced by climate change directly and indirectly and on a variety of spatial and temporal scales. Under a changing climate, many regions around the globe and especially in urban areas, have experienced increases in flood intensity and frequency in recent decades. Flooding can strain transportation networks in both the short- and long-term through transportation delays, infrastructure damage, and recovery, and potentially affect economies. The present article is a review of how flooding impacts transportation networks in both short- and long-term timescales and their subsequent impact on resiliency of the network. Firstly, flood effects are classified based on the connections between the type of flooding and the type of impact (either direct or indirect) on the transportation system. An analysis of the assessment methods and the transport models used to formulate flood effects on the transportation system is provided, as well as the drawbacks from the context of timescales, and recommendations for future research. The analysis indicates that the majority of the articles assess the direct and tangible impacts with focus on the resilience of the transportation network in short- and medium-term temporal scales and at smaller spatial scales. There is less emphasis on indirect, intangible flood impacts, and long-term temporal scales.